(untitled) (Fiep Bulletin - online, 2013)
During the process of aging, it is observed that different components of physical aptitude related to health were reduced, such as fitness, strength, muscle resistance and flexibility. Among these components, muscle strength is one of the elements that are mostly reduced with aging, resulting in the reduction of the capacity to do day-by-day activities, like carrying objects, climbing stairs, standing up the sofa, and many others. The purpose of this study was to investigate the effect of an 8- week resistance training program in the hand-grip strength in elderlies. This study is characterized as almost-experimental. The sample was composed by 40 female elderlies, with ages raging from 60 to 75 years, living in Guarapuava-PR. These participants were evaluated before and after the training program. The result of the evaluation before training was 25.05 Kgf. All the subjects increased significantly the hand-grip strength to 26,97 kgf after training, having a modification of 1,9 Kgf an average of 7,5% in the increase of hand-grip strength in elderlies.